An Intensive Perioperative Regimen of Pregabalin and Celecoxib Reduces Pain and Improves Physical Function Scores Six Weeks after Total Hip Arthroplasty: A Prospective Randomized Controlled Trial - Nicole ME Carmichael; Joel Katz; Hance Clarke; Deborah Kennedy; Hans J Kreder; Jeffrey Gollish; Colin JL McCartney (Pain Research and Management)
BACKGROUND: Despite the success of total hip arthroplasty (THA), some patients experience persistent pain and poor function after surgery. Predictors of poor outcomes include the presence of significant pre- and postoperative pain. Patients undergoing THA often experience severe, longstanding pain before surgery that may compromise the outcome of the procedure.